In vitro сlonal propagation of repairing hybrids of wild strawberry Fragaria ananassa Duch. (Experimental biology, 2018)
The features of the clonal propagation technology of repairing hybrids of wild strawberry (Fragaria ananassa Duch.) have been studied. Traditionally, the strawberry is vegetative propagated by grafting, but for the repairing varieties of strawberry, this method is less effective because plants form only 1–2 rosettes per plant during the growing season. The clonal micropropagation in vitro is the alternative method of reproduction to vegetative propagation. For the introduction of strawberry in vitro culture apical stolons and non-rooting rosettes collected from April to June have been taken.To obtain polyploid plants formed during callusogenesis process, stem and leaf explants were used. The main medium was Murashige-Skug agar medium (MS) supplemented with plant growth regulators (PGRs) and ascorbic acid (1.5 mg/l), the control medium was MS medium without PGRs. The influence of different concentration of cytokinin (0,3-1 mg/l 6-BAP) on the multiplication and auxin (0,5-1 mg/l IAA) on rooting of repairing hybrids of strawberry in vitro culture have been studied. The optimal concentrations of 6-benzylaminopurine (0.3 mg/l) were determined at the propagation stage and the same for α-indoleacetic acid (0,5 mg/l) on the rooting stage have been determined.Microrosettes with a well-developed root system obtained during in vitro cultivation were acclimatized and grown on hydroponics. Adapted to growth in the open ground plants were used as a planting material, which was propagated in a greenhouse.
Keywords: Fragaria ananassa Duch.wild strawberry, clonal micropropagation in vitro, plant growth regulators, planting material.